Persepsi Petani terhadap Sumber Risiko pada Usahatani Padi Sawah di Kecamatan Sungai Kakap - Adriyansyah, Muhammad; Kurniati, Dewi; Maswadi, Maswadi (Universitas Galuh, 2025)
Rice is one of the leading commodities in the food crop sub-sector which is being widely developed in line with the current increasing national food needs. Efforts to enhance rice production are frequently impeded by different agricultural risks. The farming sector's vulnerability to weather, climate, pest and disease issues, volatility in input and output prices, market possibilities, limited capital, and farmer management make optimal production efforts difficult to achieve. This condition has an impact on farmers' perceptions in the decision-making process for rice farming in the future. The individual characteristics of farmers also mean that perceptions in responding to the risks of farming are often different between other farmers. This study seeks to investigate farmers' opinions of lowland rice farming risks and to examine the relationship between farmer characteristics and perceptions of lowland rice farming risks in Sungai Kakap District. Data was gathered using interviews, questionnaires, and observations. This study employs quantitative descriptive methods including interval class analysis and Spearman Rank correlation. The results indicate that farmers in Sungai Kakap District exhibited negative perceptions toward the risk of lowland rice farming. Other from that, farmer factors such as education level, farming experience, and wealth have a major impact on the perception of risk in lowland rice cultivation in Sungai Kakap. Therefore, to reduce farmers' unfavorable perceptions of the dangers of lowland rice farming, it is vital to manage risks effectively and develop farmers' knowledge and skills in lowland rice farming.